OILY WATER TREATMENT USING CERAMIC MEMBERANE (Journal of Engineering, 2011)
This research was conducted using ceramic microfiltration membrane for treatment of oily wastewater in the pilot-scale dead-end filtration system designed in the laboratory under the influence of conditions of feed flow rate 15-35 l/h, feed temperature 32-48°C, oil feed concentration 300-1200 ppm, feed solution pH 2.6-9.8. The influence of these conditions on the permeate flux rate and oil rejection percent were investigated. Experimental results indicated that when feed flow rate increased to 35 l/h permeate fluxrates increased to 100 l/m2.h and oil rejection percent decreased to 70.1%, and when feed temperatureincreased to 48 ºC permeate flux rate increased to 62 l/m2.h and oil rejection percent decreased to 56.44%.But when oil feed concentration increased to 1200 ppm permeate flux rate decreased to 17.2 l/m2.h and oil rejection percent increased to 99.7%. Also basic feed solution (pH=9.8) gave high permeate flux rate(44.51 l/m2.h) and low oil rejection percent (84%) in comparison with acidic feed solution (pH=2.6) whichgave low permeate flux rate (26.42 l/m2.h) and high oil rejection percent (99.46%). Four classical modelswere investigated to flux decline and the results showed that the experimental data was consistent (R2 =0.9883) with the complete blocking filtration model.